EBI1-ligand chemokine(ELC)attracts a broad spectrum of lymphocytes: activated T cells strongly up-regulate CCR7 and efficiently migrate toward ELC - Yoshida, R (International immunology, 1998)
EBI1-ligand chemokine (ELC) is a CC chemokine constitutively expressed in various lymphoid tissues and a high-affinity functional ligand for EBI1/CCR7, a seven transmembrane G-protein-coupled receptor originally identified as an Epstein-Barr virus (EBV)-inducible gene. Here we examined chemotactic activity of ELC on peripheral blood leukocytes. ELC attracted both CD4+ and CD8+ T cells, particularly efficiently after activation with IL-2 or with phytohemagglutinin (PHA) plus IL-2, as well as CD19+ B cells, but not CD16+ NK cells, CD14+ monocytes or neutrophils. Among CD3+ T cells, ELC attracted both CD45RO- naive and CD45RO+ memory subsets. ELC also induced vigorous calcium mobilization in T cells stimulated with IL-2 with an ED50 of 3 nM. ELC fused with the secreted form of alkaline phosphatase (ELC-SEAP) specifically bound to lymphocytes and this binding was blocked only by ELC among 10 CC chemokines so far tested. Notably, lymphocytes stimulated with IL-2 or T cells expanded by PHA plus IL-2 showed much higher levels of binding than fresh lymphocytes. Consistently, CCR7 mRNA was detected in CD4+ and CD8+ T cells as well as B cells, but not in NK cells, monocytes or neutrophils, and was dramatically increased in T cells upon treatment with IL-2 or with PHA plus IL-2. Like ELC mRNA, CCR7 mRNA was expressed in various lymphoid tissues. By in situ hybridization, ELC and CCR7 mRNA were detected in the parafollicular and inner cortical regions of a lymph node, and in the parafollicular regions of an appendix. Collectively, ELC and CCR7 may be involved in the trafficking of a broad spectrum of lymphocytes, especially activated T cells, into and within various lymphoid tissues.